Association of maternal anti‐HLA class II antibodies with protection from allergy in offspring. Issue 9 (31st August 2013) - Jones, M.; Jeal, H.; Harris, J. M.; Smith, J. D.; Rose, M. L.; Taylor, A. N.; Cullinan, P.
Abstract: Background: Recent studies have suggested that the birth order effect in allergy may be established during the prenatal period and that the protective effect may originate in the mother. HLA class II disparity between mother and foetus has been associated with significantly increased Th1 production. In this study, we investigated whether production of HLA antibodies 4 years after pregnancy with index child is associated with allergic outcomes in offspring at 8 years. Methods: Anti‐HLA class I and II antibodies were measured in maternal serum ( n = 284) and levels correlated to numbers of pregnancies and birth order, and allergic outcomes in offspring at 8 years of age. Results: Maternal anti‐HLA class I and II antibodies were significantly higher when birth order, and the number of pregnancies were larger. Anti‐HLA class II, but not class I antibodies were associated with significantly less atopy and seasonal rhinitis in the offspring at age 8 years. Mothers with nonatopic (but not atopic) offspring had a significant increase in anti‐HLA class I and II antibodies with birth order. Conclusion: This study suggests that the 'birth order' effect in children may be due to parity‐related changes in the maternal immune response to foetal antigens. We have observed for the first time an association between maternal anti‐HLA class II antibodies and protection from allergy in the offspring. Further work is required to determine immunologically how HLA disparity between mother and father can protect against allergy.